The poetic look and El Rastro of Ramón Gómez de la Serna: Tradition and Modernity (Anclajes, 2016)
This paper addresses the role of the poetics of objects in relation to El Rastro by Ramón Gómez de la Serna, published in 1914. The author sketches the poetics of everyday objects in keeping with the aesthetics of the "objet trouvé," seeking to broaden and, in turn, challenge the limits of art. Both this aspect and the catalog of objects described in the work are discussed, and analysis is made of the predominant kitsch images in the text. This perspective has resulted in a new poetic viewpoint, in tune with classical avant-garde trends, contemporary aesthetic tendencies, and post-modernity.
Keywords: Ramón Gómez de la Serna; Spanish literature; kitsch; 20th century; post-modernity